Global discriminative-based nonnegative spectral clustering. (July 2016) - Shang, Ronghua; Zhang, Zhu; Jiao, Licheng; Wang, Wenbing; Yang, Shuyuan
Abstract: Based on spectral graph theory, spectral clustering is an optimal graph partition problem. It has been proven that the spectral clustering is equivalent to nonnegative matrix factorization (NMF) under certain conditions. Based on the equivalence, some spectral clustering methods are proposed, but the global discriminative information of the dataset is neglected. In this paper, based on the equivalence between spectral clustering and NMF, we simultaneously maximize the between-class scatter matrix and minimize the within-class scatter matrix to enhance the discriminating power. We integrate the geometrical structure and discriminative structure in a joint framework. With a global discriminative regularization term added into the nonnegative matrix factorization framework, we propose two novel spectral clustering methods, named global discriminative-based nonnegative and spectral clustering (GDBNSC-Ncut and GDBNSC-Rcut) These new spectral clustering algorithms can preserve both the global geometrical structure and global discriminative structure. The intrinsic geometrical information of the dataset is detected, and clustering quality is improved with enhanced discriminating power. In addition, the proposed algorithms also have very good abilities of handling out-of-sample data. Experimental results on real word data demonstrate that the proposed algorithms outperform some state-of-the-art methods with good clustering qualities. Highlights: We maximize the between-class scatter matrix. Meanwhile, we minimize the within-class scatter matrix. We integrate the geometrical structure and discriminative structure in a framework. A global discriminative regularization term added into the objective functions. The new algorithms can preserve the global geometrical and discriminative structure.